Golden opportunity, reasonable risk and personal responsibility for health - Savulescu, J (BMJ Publishing Group, 2017)
In her excellent and comprehensive article, Friesen argues that utilising personal responsibility in health care is problematic in several ways: (1) it is difficult to ascribe responsibility to behaviour; (2) there is a risk of prejudice and bias in deciding which behaviours a person should be held responsible for; (3) it may be ineffective at reducing health costs. In this short commentary, I will elaborate the critique of personal responsibility in health but suggest one way in which it could be used ethically. In doing so, I will introduce the concepts of reasonable risk and golden opportunity.